A Qualitative Exploration of On-Campus Experiences of English-Speaking Graduate International Students at a Leading Japanese University - Rakhshandehroo, Mahboubeh (Journal of International Students, 2018)
With the rapid expansion of English-medium courses/degree programs at Japanese universities over the past 15 years, a greater number of English-speaking international students from diverse backgrounds are being attracted. However, little research has been conducted to address the needs of this minority group, especially at the graduate level. Employing interpretative phenomenological analysis (IPA), this study explores on-campus satisfaction with life (SWL) of nine graduate international students studying primarily in the Englishmedium regarding the support model of their Japanese university. Four master themes of traditional support, student ideal support, challenges, and best practices are discussed. The results present effective Japanese university support strategies that can promote SWL of English-medium graduate international students.